Occurrence of enterotoxigenic Escherichia coli in the aquatic environment and impact of climatic factors - Johura, Fatema-Tuz; Sultana, Marzia; Lewis, Jade; Sadique, Abdus; Sack, David A.; Sack, Richard B.; Alam, Munirul; Chakraborty, Subhra (Frontiers in Environmental Science, 2025)
BackgroundThe prevalence of ETEC in the environment could be influenced by environmental factors, which may contribute to seasonal outbreaks. This study assessed the seasonal prevalence of the ETEC population in water bodies in relation to ecological changes in Bangladesh.MethodThe presence of ETEC in water, plankton, and sediment samples collected from water bodies in Mathbaria, a southern coastal region, was investigated using quantitative PCR (qPCR) and an extensive culture method over a year. Concurrently, the physico-chemical parameters of the water were measured. We also tested aquatic samples from Chhatak, a northern hilly region.ResultsETEC was detected in a high proportion (56%–78%) in water, plankton, and sediment samples from both sites. In Mathbaria, higher abundance of ETEC was noted in fall and spring, followed by summer and lowest in the monsoon. ETEC positivity was high in winter by qPCR, but no viable ETEC could be isolated. Environmental conditions such as neutral to low alkaline pH, elevated dissolved oxygen levels, and warmer water temperatures showed a trend of association with increased ETEC prevalence.ConclusionThe persistence of ETEC in environmental water and their association with ecologic factors may help to explain seasonal illnesses in people.